PERSEPSI WISATAWAN TERHADAP ATRIBUT DESTINASI PANTAI LAKEY DI KABUPATEN DOMPU - Nugroho, M. Setyo; Afif Al Fattah, Zuhair (Institut Agama Hindu Negeri Gde Puda Mataram, 2024)
This study aims to analyze the perceptions of domestic and foreign tourists regarding the attributes of Lakey Beach, Dompu Regency, as a tourist destination. The research uses qualitative methods and is presented descriptively. Data collection methods include direct observation of Lakey Hu'u to assess the current condition of various destination attributes, such as tourism products, support facilities, accommodations, activities, institutions, image, pricing, cleanliness, safety, comfort, and services. Additionally, interviews were conducted with ten foreign tourists and ten domestic tourists. The findings of this study indicate that, overall, tourists have a positive perception of Lakey Beach. However, some attributes, such as cleanliness and the facilities at places of worship, received negative feedback. The results of this study are intended to provide a deeper understanding of tourists' preferences and perceptions of Lakey Beach, as well as to offer insights for stakeholders involved in the development and promotion of tourism in the region.